S100P is Overexpressed in Squamous Cell and Adenosquamous Carcinoma Subtypes of Endometrial Cancer and Promotes Cancer Cell Proliferation and Invasion. (25th November 2016) - Jiang, Hongfei; Hu, Hang; Lin, Fan; Lim, Yoon Pin; Hua, Yunfen; Tong, Xiaomei; Zhang, Songying
ABSTRACT: S100P is known to affect tumor development and metastasis of various cancers, but its role in endometrial cancer is unclear. We reported that S100P expression was dramatically elevated in both endometrial squamous cell carcinoma and adenosquamous carcinoma, but not in adenocarcinoma and normal endometrial samples. Moreover, we revealed an oncogenic role of S100P promoting cell proliferation, invasion, and migration while reducing apoptosis, possibly via its upregulation and/or activation of receptors of advanced glycation end products and consequently the oncogenic PI3K-AKT and MAPK pathways. Therefore, S100P might be a specific biomarker and a potential drug target for squamous cell and adenosquamous carcinoma subtypes of endometrial cancer.